2020
DOI: 10.1289/ehp6596
|View full text |Cite
|
Sign up to set email alerts
|

Triclocarban, Triclosan, Bromochlorophene, Chlorophene, and Climbazole Effects on Nuclear Receptors: An in Silico and in Vitro Study

Abstract: BACKGROUND: Endocrine-disrupting chemicals can interfere with hormonal homeostasis and have adverse effects for both humans and the environment. Their identification is increasingly difficult due to lack of adequate toxicological tests. This difficulty is particularly problematic for cosmetic ingredients, because in vivo testing is now banned completely in the European Union. OBJECTIVES: The aim was to identify candidate preservatives as endocrine disruptors by in silico methods and to confirm endocrine recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…TCS acts as estrogenic agonist and antagonist based on the experiments conducted on various breast cancer cells (Huang et al 2014b ; Henry and Fair 2013 ). Thus, antagonist effects of TCS were also observed on glucocorticoid, androgenic and thyroid receptors (Kenda et al 2020 ). Different mechanisms of in vitro disruption of thyroid homeostasis were suggested such as dose–response inhibition of T4 to T3 conversion (Butt et al 2011 ) as well as a non-competitive inhibition of iodide uptake in rat thyroid follicular cells and thyroid peroxidase activity in rat microsomes (Wu et al 2016 ).…”
Section: Possible Adverse Effects Of Tcsmentioning
confidence: 99%
“…TCS acts as estrogenic agonist and antagonist based on the experiments conducted on various breast cancer cells (Huang et al 2014b ; Henry and Fair 2013 ). Thus, antagonist effects of TCS were also observed on glucocorticoid, androgenic and thyroid receptors (Kenda et al 2020 ). Different mechanisms of in vitro disruption of thyroid homeostasis were suggested such as dose–response inhibition of T4 to T3 conversion (Butt et al 2011 ) as well as a non-competitive inhibition of iodide uptake in rat thyroid follicular cells and thyroid peroxidase activity in rat microsomes (Wu et al 2016 ).…”
Section: Possible Adverse Effects Of Tcsmentioning
confidence: 99%
“…As shown in Figure a, CBZ significantly decreased the E2 concentration in zebrafish testes from the M-group, while the reductions in T and 11-KT levels were found in all CBZ-exposed groups ( p < 0.05). Kenda et al (2020) confirmed that CBZ is an androgen receptor antagonist, which competes with endogenous androgens for androgen receptors and thereby blocks androgens exerting their physiological functions . T and 11-KT are the most active androgens in fish, and they are required to participate in the spermatogenesis of males. , It has been reported that the reduction of T and 11-KT may change the sex differentiation, reproductive behavior, and population of fish .…”
Section: Resultsmentioning
confidence: 99%
“…TCC is widely used as an antimicrobial agent in personal care products, with an annual consumption of 200–400 tons in the United States . However, it is an endocrine-disrupting chemical that leads to adverse reproductive and developmental effects . The target analytes in this study are not only widely used in industries and daily life but also frequently detected in the aquatic environment …”
Section: Introductionmentioning
confidence: 99%